2013
DOI: 10.1111/exd.12267
|View full text |Cite
|
Sign up to set email alerts
|

A non‐coding mutation in the 5′ untranslated region of patched homologue 1 predisposes to basal cell carcinoma

Abstract: Mutations in the human homolog of the Drosophila patched gene, patched homologue 1 (PTCH-1), are responsible for most hereditary and sporadic basal cell carcinomas. Here, we present a father and daughter with a high propensity for the development of basal cell carcinoma who were heterozygous for a non-coding germline mutation in the 5′ untranslated region (UTR) of PTCH-1 (insertion of a surplus CGG triplet at the site of a seven times CGG repeat). We analysed the impact of this mutation on PTCH translation usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In a recently published analysis, the complete 188nt-long PTCH1b 5'UTR sequence, harboring either 7 or 8 CGG repeats, was cloned into pGL4.10 vector downstream of TK (thymidine kinase) promoter and upstream of Fluc. 33 The results in HEK 293T cells showed dramatically reduced reporter activity for plasmid harboring 8 CGG repeats, with no effect on Fluc transcription compared with the 7 CGGs construct. Consequently, both studies concluded that the CGG-repeat number could potentially alter the PTCH1b expression at translational level, which might have an effect on the severity of the disease in which certain CGGrepeat alleles were found.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In a recently published analysis, the complete 188nt-long PTCH1b 5'UTR sequence, harboring either 7 or 8 CGG repeats, was cloned into pGL4.10 vector downstream of TK (thymidine kinase) promoter and upstream of Fluc. 33 The results in HEK 293T cells showed dramatically reduced reporter activity for plasmid harboring 8 CGG repeats, with no effect on Fluc transcription compared with the 7 CGGs construct. Consequently, both studies concluded that the CGG-repeat number could potentially alter the PTCH1b expression at translational level, which might have an effect on the severity of the disease in which certain CGGrepeat alleles were found.…”
Section: Discussionmentioning
confidence: 87%
“…20 Up to now, the only studied potential regulatory element has been a (CGG) n repeat polymorphism present immediately upstream the AUG start site, but not clear association between repeat numbers and disease risk was found. 32,33 Here we thoroughly explored cis-element features of the 5'UTR of the PTCH1 transcript 1b applying the methodology previously used for the functional analysis of 5'UTR of the CDKN2A gene. 34 …”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous evidences demonstrating the absence of hot spot mutation in PTCH1 gene [ 51 , 52 , 53 , 54 ], molecular analysis of patients enclosed in this study recorded heterozygotic genetic variation distributed along the entire coding sequence ( Table 1 ). Among these mutations, eight were missense changes resulting in harmful or pathogenic effects based on data from online databases ( , and , accessed on 20 June 2021), 1 was a deletion resulted in a frameshift of the coding sequence, and one insertion of a surplus CGG triplet was at the site of seven times CGG repeat in a functionally important 5′UTR intron region involved in PTCH1b variant transcription and translation [ 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Major genetic changes causing BCC include inactivating mutations of PTCH-1 and activating mutations of Smoothened (27,28). Vismodegib is a small molecule that is able to inhibit Smoothened, and is commonly used in the treatment of advanced BCCs (29,30). A mounting body of evidence has demonstrated that, in a number of solid tumours, the ligand-dependent activation of HH signalling is potentiated through cross-talk with other critical molecular signalling pathways (31).…”
Section: Biology Of Nmsc and The Rationale For Using Targeted Therapymentioning
confidence: 99%